Study on the Keeping Quality of Functional Spent Broiler Breeder Hen Chicken Sausages at Refrigeration Temperature - Indumathi, J.; Shashikumar, M.; Bhaskarreddy, G. V.; Babu, A. Jagadeesh; Gnanprakash, M. (International Journal of Bio-resource and Stress Management, 2022)
The present research was carried out in the Department of Livestock Products Technology, College of Veterinary Science, Tirupati, Andhra Pradesh, India during 2018–2019.The objective of this study was to assess the keeping quality of aerobically packed functional chicken sausages under refrigeration by using ground vegetable oilseeds on physico-chemical, proximate, microbiological and sensory properties of the product.Low-fat chicken sausages incorporated with three different ground vegetable oilseeds (poppy, sesame and peanut) at 10% level were developed and analyzed for their keeping quality along with high fat control under aerobic packaging conditions kept at chilling (4±1°C) temperature until spoilage. The mean values of FFA, TBARS, Tyrosine, standard, psychrophilic, yeast and moulds plate count for all for sausages were significantly (p<0.05) influenced by formulation and storage period and were increased significantly (p<0.05) throughout storage period irrespective of the formulations, while formulation did not show any significant influence on pH. Regardless of formulation, coli forms, lactobacillus and anaerobic counts could not be detected in all sausages throughout storage period. Sensory attributes showed a significantly (p<0.05) decreasing trend for both control as well as low-fat chicken sausages throughout storage period. Formulation had no significant influence on sensory parameters of chicken sausages throughout the storage period but were significantly (p<0.05) influenced by storage period. Study concluded that all three ground vegetable oil seed are effective in checking the lipid oxidation and microbial growth and preserving sensory quality during the storage period and among them sesame seed paste was proved to be a preferred preservative.